Mean stress effect correction in strain energy-based fatigue life prediction of metals. (November 2017) - Zhu, Shun-Peng; Lei, Qiang; Huang, Hong-Zhong; Yang, Yuan-Jian; Peng, Weiwen
A new mean stress corrected strain energy model is proposed for fatigue life prediction of metals. Specifically, a mean stress sensitivity parameter is incorporated into modify the dissipated strain energy by introducing two mean stress correction factors. The prediction accuracy of the proposed model is compared with those of Walker, Smith–Watson–Topper, Morrow, and generalized damage parameter models by using 13 experimental data sets. All data points for each material are, respectively, fitted into a single mean stress corrected strain energy-life curve. More accurate predictions are achieved by the proposed model for all data sets with lower model prediction errors than others.